2020
DOI: 10.1038/s41598-020-73380-x
|View full text |Cite
|
Sign up to set email alerts
|

Sources of predictive information in dynamical neural networks

Abstract: Behavior involves the ongoing interaction between an organism and its environment. One of the prevailing theories of adaptive behavior is that organisms are constantly making predictions about their future environmental stimuli. However, how they acquire that predictive information is still poorly understood. Two complementary mechanisms have been proposed: predictions are generated from an agent’s internal model of the world or predictions are extracted directly from the environmental stimulus. In this work, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…This tight link has been established before. 31 , 32 , 33 , 34 , 35 , 36 In our work, the link can be explained in the following way: the preactivation allows “predictive inhibition” while forcing the network weights to be as small possible so that irreducible noise has as little impact as possible on the network activity. We refer the reader to the supplemental information for a derivation of why this is the case.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This tight link has been established before. 31 , 32 , 33 , 34 , 35 , 36 In our work, the link can be explained in the following way: the preactivation allows “predictive inhibition” while forcing the network weights to be as small possible so that irreducible noise has as little impact as possible on the network activity. We refer the reader to the supplemental information for a derivation of why this is the case.…”
Section: Resultsmentioning
confidence: 99%
“… 34 demonstrated that a system with memory exposed to a stochastic signal must be predictive to operate at maximal energy efficiency. Candadai and Izquierdo 35 showed, information theoretically, that predictable environments produce neural networks that exhibit predictive information. In the work by Sengupta et al., 60 the minimization of thermodynamic energy was linked to information processing and efficiency using the Jarzynski equality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NSCs consist of recurrent neural networks (RNNs) organized into a predictive hierarchy, where each RNN attempts to predict data from the level below, and where only unpredicted information is passed upwards. These predictions are realized in the form of recurrent dynamics (Candadai & Izquierdo, 2020;Lu & Bassett, 2020), whose unfolding entails a kind of search processes via competitive/cooperative attractor formation over states capable of most efficiently responding to-or resonating with (Rumelhart & McClelland, 1987;Safron, 2020b)ascending data streams. In this way, much as in FEP-AI, predictive abilities come nearly "for free" via Hamilton's principle of least action (Ali et al, 2021;K.…”
Section: Fep-ai and Aixi: Intelligence As Prediction/compressionmentioning
confidence: 99%
“…For example, PID has been used to demonstrate a relationship between synergy and feed-back information flow in mouse organotypic cultures [69], to show significant synergy between somatic and apical dendritic output of L5b pyramidal neurons and its relationship to activation of dendritic GABA B receptors in rat S1 slices [68], and to estimate unique contributions of acoustic features of speech to BOLD responses in humans [22, 23]. Further, it has been used to explore the structure of simulated input-driven recurrent network models [16] and artificial generative neuronal networks [75]. We believe that PID will be increasingly applied in coming years, especially in studies addressing non-linear confounding effects, the specificity of functional relations, and synergistic encoding.…”
Section: Introductionmentioning
confidence: 99%